2008
DOI: 10.1007/s11162-008-9116-5
|View full text |Cite
|
Sign up to set email alerts
|

Situational and Personal Causes of Student Cheating

Abstract: The causes of students' academic dishonesty behavior were explored using survey and experimental vignette methods. Participants were surveyed about their own cheating behavior, neutralizing attitudes, performance/mastery orientation and perceptions of peer attitudes and behavior. As predicted, neutralizing attitudes influenced cheating behavior directly, but also indirectly, increasing the effect of individual attitudes. Observing others cheating was strongly correlated with one's own cheating behavior. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
138
2
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(159 citation statements)
references
References 22 publications
10
138
2
9
Order By: Relevance
“…Numerous studies have used brief scenarios or statements to depict examples of academic misconduct 9,29,[33][34][35] in which students were presented with between 9 and 24 scenarios. Compared with the first-person approach, 9 our reference to fictitious characters was arguably more likely to depersonalize the situation and enable exploration of students' perceptions in cases of ambiguity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have used brief scenarios or statements to depict examples of academic misconduct 9,29,[33][34][35] in which students were presented with between 9 and 24 scenarios. Compared with the first-person approach, 9 our reference to fictitious characters was arguably more likely to depersonalize the situation and enable exploration of students' perceptions in cases of ambiguity.…”
Section: Discussionmentioning
confidence: 99%
“…1 The incidence of and demographic factors associated with academic misconduct in postsecondary students, predominantly cheating in assessments and plagiarism, have been extensively studied by academic researchers. [2][3][4][5][6][7][8][9][10][11] Factors including age, sex, and experience with postsecondary study are still debated in the literature. 12 Some studies have found that male students are more likely than female students to commit plagiarism, [13][14][15] although this has been contradicted.…”
Section: Introductionmentioning
confidence: 99%
“…Student cheating has been strongly correlated with the observation of others cheating (Fulks et al 2010;O'Rouke et al 2010;Rettinger & Kramer 2009). In this regard, theorists have suggested that the broader institutional culture must be targeted to promote the spirit of integrity (Imran & Nordin 2013;Piascik & Brazeau 2010) and that the dishonesty of academic faculty themselves must be addressed (Parameswaran 2007).…”
Section: Reasons For Student Academic Dishonestymentioning
confidence: 99%
“…Cheating has been linked to students who evidence low grades (Hensley et al 2013), to those who lack self-confidence and have low self-esteem (Pittam et al 2009), to those who lack knowledge of how to avoid cheating (Granitz & Loewy 2007;Voelker et al 2012), and to those who are extrinsically motivated (Rettinger & Kramer 2009). Behaviour laziness or lack of conscientiousness (De Bruin & Rudnick 2007) and an inherent lack of integrity (Evering & Moorman 2012), have all been linked to student cheating.…”
Section: Reasons For Student Academic Dishonestymentioning
confidence: 99%
“…These perceptions and beliefs often result from neutralization techniques (Haines et al, 1986;Sykes & Matza, 1957). Positively associated with academic dishonesty, neutralizing techniques allow individuals to justify their behaviors despite knowing such behaviors to be unethical or violative of institutional integrity policies (Rettinger & Kramer, 2009;Sykes and Matza, 1957). For instance, students may claim "ʻI'll never need to use this material' and 'Everyone else is doing it'" (O' Rourke et al, 2009, p. 49) to justify their actions.…”
Section: Attitudes Regarding Cheatingmentioning
confidence: 99%